Controlling the Morphology of Poly(ethylene glycol)-b-poly(lactide) Self-Assemblies in Solution: Interplay of Homopolymer Additives and Kinetic Traps - Pei Qi Lim; Srirangam Ramanujam Vaibavi; Atul N. Parikh; Subbu Venkatraman; Bertrand Czarny (Nanomaterials)
This study investigates the effects of homopolymer additives and kinetic traps on the self-assembly of poly(ethylene glycol)-b-poly(lactide) (PEG-PLA) block copolymer (BCP) nanostructures in aqueous environments. By using non-adsorbing PEG homopolymers to kinetically trap PEG-PLA nanostructures, we demonstrate that varying the concentration and molecular weight of the added PEG induces a reversible micelle-to-vesicle transition. This transition is primarily driven by changes in the molecular geometry of the PEG-PLA BCPs due to excluded volume screening effects. Additionally, the reversible vesicle-to-micelle transition upon PEG’s removal shows time and temperature dependency, highlighting the influence of the system’s kinetic nature. Intermediate structures observed during the transition support a mechanism based on shifts in the molecular geometry of PEG-PLA. As a proof of concept, we show that PEG-PLA vesicles can act as thermoresponsive delivery systems, retaining dye at low temperatures (4 °C) and releasing it upon heating (37 °C). Overall, this work presents a novel approach to controlling BCP nanostructures’ morphology, with implications for drug delivery and material science applications.